Genetics and conservation of rare and endemic plants: the case of "Genista sanabrensis" (Fabaceae) in the Iberian Peninsula - Cires, Eduardo; Sanna, Mauro; M. Vázquez, Víctor; Fernández Prieto, José Antonio (Mediterranean Botany, 2018)
Genista sanabrensis Valdés Berm., Castrov. & Casaseca (Fabaceae) is an endemic and rare species of the Northwestern Iberian Peninsula. Despite its limited distribution, the species is locally abundant and therefore not categorized by the IUCN criteria as threatened at the national level. However, comprehensive studies on the genetic diversity and structure of rare and endemic species from Iberian Peninsula are urgently needed to promote effective conservation and management activities. Therefore, we conducted amplified fragment length polymorphism (AFLP), nuclear rDNA (ITS, ETS) and plastid regions (trnL, trnL-F, matK, rbcL) analyses to characterize the genetic diversity and variation of this species within and between populations. Our results confirm the monophyly of the species compared to closely related taxa. The presence of insertions/deletions together with point mutations makes the northern populations indispensable in the elaboration of conservation strategies. Genetic diversity was moderate/low, although the survival of these populations at the genetic level shows no signs of being threatened. This study provides important insights into the genetic structure of G. sanabrensis with potential applications to its effective conservation.